Guidelines for the effective use and procurement of advanced warning arrow panels. - Mace, Douglas J.; Finkle, Mark.; Pennak, Sara.; National Research Council (U.S.). Transportation Research Board; National Cooperative Highway Research Program; Texas Transportation Institute (Washington, D.C. Transportation Research Board, National Research Council, 2001)
This digest summarizes the results of NCHRP Project 5-14, "Advanced warning arrow panel visibility" ... [and] is based on a draft final report prepared by Douglas Mace, Mark Finkle, and Sara Pennak ...
Caption title.
October 2001.
Includeds bibliographical references (p. 12).
Keywords: Traffic signs and signals -- United States -- Design and construction; Visibility; arrows (signals); flashing traffic signals